SEJARAH KRONOLOGI BAHASA ARAB: SEMITIK - Nasrulloh, Muhamad (TARBAWI:Journal on Islamic Education, 2023)
The chronology of the development of Arabic can be traced back to the early Semitic languages spoken in the Mesopotamia and Levant regions around 3000 BC. The language underwent a significant transformation along with migration and interaction between ethnic groups in the Arabian Peninsula and beyond. Important stages in the history of the Arabic language include the period of the Old Arabic language, documented in ancient inscriptions and inscriptions, to the development of Classical Arabic in the 6th century AD which became the language of the Quran. The role of Islam and the expansion of the Arab Caliphate extended the use of this language to a wider area, thus becoming the lingua franca in science, literature, and government in the Islamic world. Standard Modern Arabic, as it is used today, is the result of an evolution of Classical Arabic with adaptations and simplifications for contemporary communication. The chronology of the development of Arabic as part of the Semitic language family shows how this language is not only a means of communication, but also a symbol of identity and cultural heritage that continues to evolve and adapt to socio-political dynamics With the advent of Islam in the 7th century AD, Classical Arabic, which is the language of the Quran, became the linguistic and cultural standard that united the Arab region. The spread of Islam and the expansion of the Umayyad and Abbasid Caliphate led to Arabic becoming the lingua franca in a wide area, from Spain to Central Asia, replacing local languages in the context of government, science, and commerce. During this period, the Arabic language also experienced rapid development in the fields of literature, philosophy, science, and law, known as the Islamic Golden Age.